2020
DOI: 10.3168/jds.2019-16523
|View full text |Cite
|
Sign up to set email alerts
|

Differential somatic cell count as an additional indicator for intramammary infections in dairy cows

Abstract: Mastitis, often caused by intramammary infection (IMI), is a significant problem in dairy farming globally. Somatic cell count (SCC) is widely used as a parameter for screening IMI in cows that are then treated or culled. We investigated the potential of a new parameter, differential SCC (DSCC), to detect IMI at cow level when SCC is already known. We achieved this using bacterial culture (BC) and PCR to detect 4 categories of pathogens (major, minor, other, and any) in 2 Danish dairy herds. Quarter milk sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 27 publications
2
41
2
1
Order By: Relevance
“…The trend analysis showed a decrease of DSCC with increasing DIM when SCC was ≤50,000 cells/mL, but no significant trends were observed at higher SCC levels ( Table 7 ). These data did not agree with the results of studies applying flow-cytometry [ 29 ], neither with the ones from a recent study applying the same instrument as in this study [ 14 ]. However, in the latter case, data were not ranked by SCC levels.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The trend analysis showed a decrease of DSCC with increasing DIM when SCC was ≤50,000 cells/mL, but no significant trends were observed at higher SCC levels ( Table 7 ). These data did not agree with the results of studies applying flow-cytometry [ 29 ], neither with the ones from a recent study applying the same instrument as in this study [ 14 ]. However, in the latter case, data were not ranked by SCC levels.…”
Section: Discussioncontrasting
confidence: 99%
“…The availability of a sample size larger than the ones reported even in recent studies on DSCC [ 14 , 15 , 16 , 24 , 28 ] and the period of time during which samples were collected allows to investigate the pattern of cell types during the course of the whole lactation. The statistical model applied for evaluating factors affecting DSCC variability in a healthy subset showed that, among random factors, the herd has a very low influence, while all fixed factors considered, as well as their interactions showed a statistically significant influence ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirkeby et al (26) found a significant association between F-DSCC and both DIM and lactation number. F-DSCC generally decreased over the course of the lactation, and the relationship between F-DSCC and lactation number was found ambiguous (26).…”
Section: Factors Affecting Dsccmentioning
confidence: 96%
“…Given that there is no true gold standard for the diagnosis of mastitis or IMI (Adkins & Middleton, 2018), we focused on inflammation rather than infection and considered SCC as a gold standard to perform ROC analysis, as previously done by Zecconi et al (2019). Investigations on DSCC for the identification of IMI have been recently conducted by Kirkeby et al (2019) and Schwarz et al (2019), who concluded that DSCC can add significant information on IMI and that obtained results justify further studies on the combined use of DSCC and SCC to detect IMI.…”
Section: Receiver-operating Characteristic Curves For Repeated Measuresmentioning
confidence: 99%